Balancing food security and ecological protection through the spatial reconfiguration of cropland and forestland under a regional area balance constraint - Junjun Zhu; Xiaobin Jin; Houbao Fan (Agricultural Systems, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

Differentiated landscape pattern transformation strategies drive territorial space carbon neutrality: A path exploration based on mixed land use units - Houbao Fan; Xiaobin Jin; Junjun Zhu; Zhouyao Zhang; Chunguang Hu; Han Hu; Xiaoya Du; Yinkang Zhou (Sustainable Cities and Society, 2025)

Machine learning-based sweet spot prediction for lacuscrine shale oil in the Weixinan Sag, Beibu Gulf Basin, China - Ruoxin Huang; Yifan Li; Zhiqian Gao; Caiwei Fan; Junjun You; Ruisi Li; Chengkun Deng; Guocui Li (Marine and Petroleum Geology, 2025)

Zebrafish larvae as a model for investigating dual effects of fluoride on bone development - Xin Wang; Junjun Li; Yumei Fan; Xiaodi Zhang; Yanmei Yang; Yanhui Gao (Toxicology and Applied Pharmacology, 2025)

Distribution characteristics, source analysis and ecological risk assessment of PAHs in tea garden soil in China - Jinzhi Li; Jiantao Xue; Yan Tan; Mingmin Jia; Junjun Feng; Xueqing Feng; Ningguo Zheng; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Insights from Computational Fluid Dynamics and In Vitro Studies for Stent Protrusion in Iliac Vein: How Far Shall We Go? - Zhenmin Fan; Jian Lu; Hao Cheng; Xia Ye; Xiaoyan Deng; Pengfei Zhao; Junjun Liu; Mingyuan Liu (Cardiovascular Engineering and Technology, 2025)

Molecular insights into the binding mechanism of strontium and cesium on phyllosilicates with different expandability - Junjun Hou; Xiaolan Zhao; Qi Tan; Peng Wang; Xinyi Shi; Qiaohui Fan; Duoqiang Pan; Wangsuo Wu (Science of The Total Environment, 2024)

Desalination of dye and protein by Ba2+/Ca2+ co-crosslinked alginate filtration membrane loaded on polypropylene non-woven - Ningning Gao; Qian Zhang; Yingqi Fan; Zhihui Chen; Yue Zhang; Junkui Gao; Junjun Shi; Huiguo Wang; Kongyin Zhao; Ligang Lin (Desalination, 2024)

Study on the characteristics of urban background ozone pollution based on long-term observations from mountain sites in China during 2015–2022 - Wei Zhao; Bo Gao; Junjun Deng; Jiaren Sun; Laiguo Chen; Shaojia Fan (Atmospheric Research, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

High acidity notably influences acid mine drainage treatment performance in constructed wetlands packed with composite organic substrates by affecting both abiotic and biotic routes - Deshou Cun; Shengjiong Deng; Xuan Li; Fan Yang; Junjun Chang; Pengchang Duan; Changqun Duan (Chemical Engineering Journal, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Temperature sensitivity of aerobic and anaerobic organic carbon mineralization varies with climate and soil depth in riparian zones - Mingzhu Lu; Gang He; Lei Fan; Guihua Liu; Junjun Wu; Wenzhi Liu; Lin Ma (Soil Biology and Biochemistry, 2024)

Metal vacancies and self-reconstruction of high entropy metal borates to boost the oxygen evolution reaction - Mengyuan Zhang; Kongliang Luo; Yaning Fan; Xiaoyan Lu; Jian Ye; Nana Lu; Jiali Dong; Qiang Niu; Junjun Zhang; Pengfei Zhang; Sheng Dai (Chemical Engineering Journal, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

Numerical investigation on NO formation of staged oxy-fuel combustion in a 35 MW large pilot boiler - Junjun Guo; Teng Guo; Tai Zhang; Fan Hu; Pengfei Li; Zhaohui Liu (Fuel, 2024)

The Probability Density Function Related to Shallow Cumulus Entrainment Rate and Its Influencing Factors in a Large-Eddy Simulation - Lei Zhu; Chunsong Lu; Xiaoqi Xu; Xin He; Junjun Li; Shi Luo; Yuan Wang; Fan Wang (Advances in Atmospheric Sciences, 2024)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

Mitochondria-associated endoplasmic reticulum membranes participate mitochondrial dysfunction and endoplasmic reticulum stress caused by copper in duck kidney - Junjun Peng; Xueyan Dai; Huiqin Fan; Chenghong Xing; Yu Zhuang; Xiaona Gao; Huabin Cao; Guoliang Hu; Fan Yang (Environmental Science and Pollution Research, 2023)

Lattice stain dominated hydrazine oxidation reaction in single-metal-element nanosheet - Jie Shi; Qintao Sun; Wenxiang Zhu; Tao Cheng; Fan Liao; Mengjie Ma; Junjun Yang; Hao Yang; Zhenglong Fan; Mingwang Shao (Chemical Engineering Journal, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

Effects of farmland use transition on soil organic carbon in dry farming areas - Ligang Lyu; Junjun Zhu; Hualou Long; Kaihua Liao; Yeting Fan; Junxiao Wang (Environment, Development and Sustainability, 2023)

Relationship between meteorological factors and mortality from respiratory diseases in a subtropical humid region along the Yangtze River in China - Lingxiang Yu; Junjun Zhu; Ming Shao; Jinian Wang; Yubo Ma; Kai Hou; Huijun Li; Jiansheng Zhu; Xiaoyun Fan; Faming Pan (Environmental Science and Pollution Research, 2022)

A Hybrid Dynamic Method for Conflict-Free Integrated Schedule Optimization in U-Shaped Automated Container Terminals - Bowei Xu; Depei Jie; Junjun Li; Yunfeng Zhou; Hailing Wang; Huiyao Fan (Journal of Marine Science and Engineering, 2022)
Automated guided vehicles (AGVs) in the U-shaped automated container terminal travel longer and more complex paths. The conflicts among AGVs are trickier. The scheduling strategy of the traditional automated container terminal is difficult to be applied to the U-shaped automated container terminal. In order to minimize the handling time of all tasks and avoid AGV conflicts simultaneously in the U-shaped automated container terminal, this paper establishes a hybrid programming model for conflict-free integrated scheduling of quay cranes, AGVs, and double-cantilever rail cranes in the unloading process. It consists of a discrete event dynamic model and a continuous time dynamic model. An improved genetic seagull optimization algorithm (GSOA) is designed. A series of numerical experiments are conducted to verify the effectiveness and the efficiency of the model and the algorithm. The results show that the proposed method can simultaneously realize the AGVs collision avoidance and multi-equipment integrated scheduling optimization in the U-shaped automated container terminal.

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Sevoflurane-Induced Neurotoxicity in the Developing Hippocampus via HIPK2/AKT/mTOR Signaling - Lirong Liang; Ze Fan; Danyi He; Youyi Zhao; Tian Zeng; Bing Liu; Tianyuan Ma; Junjun Kang; Hui Zhang (Neurotoxicity Research, 2022)

Contrasting soil C and N dynamics inferred from δ13C and δ15N values along a climatic gradient in southern China - Jiao Feng; Fan Yang; Junjun Wu; Qiong Chen; Qian Zhang; Xiaoli Cheng (Plant and Soil, 2020)

Soil labile and recalcitrant carbon and nitrogen dynamics in relation to functional vegetation groups along precipitation gradients in secondary grasslands of South China - Adugna Feyissa; Fan Yang; Jiao Feng; Junjun Wu; Qiong Chen; Xiaoli Cheng (Environmental Science and Pollution Research, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Mechanisms Underlying the Regulation of Root Formation in Malus hupehensis Stem Cuttings by Using Exogenous Hormones - Wangxiang Zhang; Junjun Fan; Qianqian Tan; Mingming Zhao; Fuliang Cao (Journal of Plant Growth Regulation, 2017)

Analysis of finite element method on mechanical properties of wheat kernel - Feng Jia; Jinshui Wang; Pei Fan; Haicheng Yin; Junjun Guan; Mengqing Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Comparative transcriptome profiling of potassium starvation responsiveness in two contrasting watermelon genotypes - Molin Fan; Yuan Huang; Yaqin Zhong; Qiusheng Kong; Junjun Xie; Mengliang Niu; Yong Xu; Zhilong Bie (Planta, 2014)

Determination of GABAAα1 and GABAB1 receptor subunits expression in tissues of gilts during the late gestation - Zhiyong Fan; Yonghui Chen; Junjun Wang; Jinping Deng; Dexing Hou; Tiejun Li; Lingyuan Yang; Zhonghua Liu; Xiaosong Wu (Molecular Biology Reports, 2013)